The impact of the fertilization system on fertility of drained sod-podsolic soil in a short-term crop rotation - Savchuk, O.; Melnychuk, A.; Drebot, O.; Kudryk, A.; Zubova, O. (Land Management, Cadastre and Land Monitoring, 2020)
The relevance of research is connected with the effective use of drained land in the face of climate change. Goal. To determine the optimized fertilizer system and to study its effectiveness on the fertility of sod-podzolic soil in short-term rotation: soybean - winter wheat - sunflower - buckwheat. Methods. Field, statistical, laboratory. Results. During the vegetation periods of 2016-2019, the sunflower was the least responsive to the soil-air drought, which, on the recommended standard N60P60K90 background, combined with 40 t/ha of manure and the increased rate N90P90K135 and 4.0 tonnes of precursor by-products provided seed yield levels 2.3 and 2.4 t/ha respectively. The maximum harvest produce from 1 ha of crop rotation area is marked on a raised background (N62P84K96 + 3.3 tonnes of by-products) - 3.20 tonnes of grain units. Conclusions. An alternative fertilizer system (replacement of 10 tons of manure per1 ha of arable land by 3.3 tons of by-products on the mineral fertilizers background) provided a positive balance of nutrients and humus in short-tecropm rotation. Prospects. Further scientific studies expect to reduce the amount of phosphorus and potassium fertilizers that provided by the by-products plowing of all crops in rotation. Keywords: drained sod-podzolic soils, short-term crop rotation, market crops, fertilizers, productivity, soil fertility